Compare the Frequency of Surgical Site Infections Following Irrigation of Appendectomy Wounds with Sterile Saline Solution Vs Imipenem Solution - Ahmad Zeb, Muhammad Shoaib Khan, Atif Iqbal, Aamir Khan, Irfan Ali, Munir Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to compare the frequency of surgical site infection following appendectomy wound irrigation with imipenem solution versus ordinary saline solution. Study Design: Randomized/ Prospective study Place and Duration: This prospective randomized study was conducted at Department of Surgery, Jinnah International Hospital, Abbottabad and MTI Hayatabad Medical Complex Peshawar in the period from 01 July, 2022 to 31 December, 2022. Methods: Total 106 patients of acute appendicitis who underwent for appendectomy were included. After getting informed written consent detailed demographics of enrolled cases were recorded. Patients were categorized in two groups. Fifty-three cases of group I received imipenem solution at closure of wound and group II was irrigated with saline solution in fifty three cases. Patients were followed for surgical site infection and the development of deep abscesses after surgery. Results: In all there were majority 63 (59.4%) males and 43 (40.6%) females. Patients mean age in group I was 26.7±3.43 years and had mean BMI 22.15±11.23 kg/m2 while in group II mean age was 25.16±6.39 years with mean BMI 21.14±16.44 kg/m2. Frequency of catarrhal inflammation was 47 (88.7%) in group I and 44 (83.02%) in group II followed by perforated appendix and gangrenous appendix. Frequency of SSI in group I was lower found in 4 (7.5%) as compared to group II in 8 (15.1%) cases with p value <0.005. There was no any significant difference observed in abscess formation among both groups Conclusion: In this study, we came to the conclusion that irrigation with imipenem solution can aid to lessen wound infection following appendectomy. It is simple to do and can lower medical expenses as well as patients' suffering from infections. Keywords: Wound irrigation with saline, Imipenem solution, Appendectomy wound infection